(3cJGH aj GdJTQjMs - (3Ydj Hf EHQGgje GdcaQ WCHjs
(3ChdgG (B:s
(3GdMeO ddg GdhGMO GdeYHhO deXgQ ef GdYOe aGdOe efGdghGA hgh MGQ QWH hGdHdZe ef GdeGA hgh HGQO QWH s
(3BNQgG (B:s
(3dGfgG JJe GdfbU GdWHjYi GdPi ai GdEfSGf HeG jMUd HgG ef GdJYdje hMaX GdYdhe hGdGQcGf s
(3eUOQ GbJfGA GdCUd (B:s
(3WH (B((3CNdGb JjehQ (B29) s
Keywords: (3GdSjGSI hGdGLJeGYs